The macroeconomic consequences of artificial intelligence: A theoretical framework - Xu Huang; Yan Hu; Zhiqiang Dong (Kiel Institute for the World Economy (IfW), 2019)
The authors explore the impact of artificial intelligence on the economy by improving the neoclassical production function and the task-based model. Based on the capital accumulation of artificial intelligence and technological progress, they present a theoretical model that explores the effect of alternative and complementary artificial intelligence on wages, capital prices, labor share, capital share and economic growth. The model shows that artificial intelligence capital lowers the capital prices and increases wages. In addition, if artificial intelligence and labor force are complementary, artificial intelligence capital has a positive impact on labor share, but if artificial intelligence and labor force can substitute each other, labor share is negatively influenced by artificial intelligence capital. The authors extend the task-based model and find that technological progress increases both wages and labor share by generating new tasks. In the long run, without consideration of exogenous technology, as the artificial intelligence capital accumulates, per capita output, per capita traditional capital and per capita artificial intelligence capital grow at the same rate, and economic growth finally reaches steady state equili- brium. With exogenous technology considered, artificial intelligence technology improves, and sustained economic growth is achieved.
Keywords: J23; J24; 330; artificial intelligence; automation; economic growth; share of labor